Penerapan Prinsip 3R dan 6R dalam Penyaluran Kredit untuk Meminimalisir NPL (Non Performance Loan) dan Meningkatkan Profitabilitas (Studi Kasus pada Bank BTN Cabang Balikpapan) - Totok Ismawanto; Hasto Finanto (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Negeri Balikpapan., 2019)
The main purpose of this study is to describe how the process of developing the principles of 3R and 6C in lending to customers, as well as its relationship with NPL and profitability of PT.Bank Tabungan Negara, Tbk, Balikpapan.This research was conducted at PT.Bank Tabungan Negara, Tbk.Balikpapan. The research method is used survey method, by using data collecting techniques of interview, questioner, observation and documentation. Object or population of this research is the financial report of PT.Bank Tabungan Negara, Tbk., which has been published and sampling using purposive sampling technique.In the data analysis, the researcher performs steps such as reduction data, presentation data, and drawing conclusion / verification. With information extracted from various sources of presentation and verification, the conclusions can be drawn: (1) 3R principles and 6C developed by PT.Bank Tabungan Negara, Tbk., Balikpapan in effective lending to minimize NPLs and to increase profitability; (2) There is a positive relationship between the development of the 3R and 6C principles with the effort to minimize the NPL level; (3) There is a positive relationship between the development of 3R and 6C principles with increased profitability.The advice given in this research is Pt.Bank Tabungan Negara, Tbk., Balikpapan needs to develop 3R, 6C principle, and other principle in lending to minimize NPL and increase profitability